Strategi Konten Produk Kalaborasi Melalui Instagram - Koni Maifa Hamida; Indri Rachmawati (UNISBA Press, 2023)
Abstract. The development of the times makes communication technology and the flow of information grow rapidly. Rapid technological changes not only affect the flow of information, but also on the increasing flow of industries, one of which is the beauty industry. The use of Instagram social media can be used as digital marketing communication. One of the local cosmetic and skincare brands that uses social media as the main medium for their digital marketing communications is Mad for Makeup. Social media with all its advantages can help in the marketing communication process. One of the social media that is widely used for marketing communication activities is Instagram. This study discusses the use of Instagram as a marketing communication medium carried out by Mad for Makeup on its collaboration product,